Edukasi Pencegahan Banjir Rob dengan Green Technology di Kelurahan Berok Nipah, Padang Barat, Sumatera Barat - Suci Fitria Rahmadhani Z; Vina Lestari Riyandini; Suci Handayani; Riko Ervil; Elmawati Elmawati; Boby Rachman; Veny Wedyawati; Afni Nelvi; Lili Hindayani (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Insufficient sanitation in densely populated residential areas in Berok Nipah Village, especially the Muaro settlement, which is directly adjacent to the river estuary and beach, results in this area often having problems in the form of tidal floods that always carry debris into the village. A lack of land causes people to settle in areas adjacent to rivers and beaches. This activity aims to provide new understanding and information to the community regarding green technology and tidal flood prevention education to communities affected by tidal floods in residential areas. Education about tidal floods in the form of counseling, socialization, and discussion about green technology (rainwater harvesting, bipolar holes, and rain gardens) to the community as a form of activity to prevent natural disasters in the form of tidal floods in Berok Nipah Village. The existence of this educational activity allows the community to apply environmentally friendly technologies such as rainwater harvesting, bipolar holes, and rain gardens to prevent and reduce the impact of tidal flooding in the Berok Nipah Village community settlements.